2016
DOI: 10.1002/app.44454
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of cellulose triacetate membranes via thermally induced phase separation

Abstract: A series of cellulose triacetate (CTA) membranes were prepared via thermally induced phase separation (TIPS) process with dimethyl sulfone (DMSO2) and polyethylene glycol (PEG400) as a crystallizable diluent and an additive, respectively. The phase separation behavior of CTA/DMSO2/PEG400 ternary system was investigated in detail by optical microscopy, differential scanning calorimetry and wide angle X-ray diffraction. This ternary system dynamically undergoes solid-solid phase separation and thus the CTA membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…Addition of PEG 400 to the support layer was conducted to fabricate a TFC FO membrane, and it was found that the addition of 6 wt% PEG was needed to reach the highest water flux [23] when DI water and 2 M NaCl were used as feed and draw solution. PEG 400 and dimethyl sulfone (DMSO 2 ) were used as an additive and a crystallizable diluent to fabricate the CTA support layer of an FO membrane through thermally induced phase separation, and the FO membrane exhibited better antifouling properties than PSf-based FO membranes [24]. Sharma et al used PEG 4000 and 6000 as additive to prepare cellulose acetate flat asymmetric FO membranes, and the modified FO membranes were used to evaluate power density performance in pressure-retarded osmosis [25].…”
Section: Peg In the Support Layer Of An Fo Membranementioning
confidence: 99%
“…Addition of PEG 400 to the support layer was conducted to fabricate a TFC FO membrane, and it was found that the addition of 6 wt% PEG was needed to reach the highest water flux [23] when DI water and 2 M NaCl were used as feed and draw solution. PEG 400 and dimethyl sulfone (DMSO 2 ) were used as an additive and a crystallizable diluent to fabricate the CTA support layer of an FO membrane through thermally induced phase separation, and the FO membrane exhibited better antifouling properties than PSf-based FO membranes [24]. Sharma et al used PEG 4000 and 6000 as additive to prepare cellulose acetate flat asymmetric FO membranes, and the modified FO membranes were used to evaluate power density performance in pressure-retarded osmosis [25].…”
Section: Peg In the Support Layer Of An Fo Membranementioning
confidence: 99%
“…Cellulose Triacetate (CTA) has been using as popular polymeric membrane material for preparation of ultrafiltration membranes in dialysis, reverse osmosis and Forward Osmosis (FO) since 1960s due to its good desalting properties, suitable toughness, high biocompatibility and cost effectiveness. CTA membranes also possess hydrophilic character thus plays an important role in fouling mitigation [35].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 lists the FRR , DR t , and DR ir values of the PSf and PSf-3BL membranes. Among them, DR ir reflects the irreversible fouling, which is very difficult to be eliminated by the hydraulic washing, and the main challenge in the membrane separation [44,47]. Overall, membranes with lower DR ir , DR t , and higher FRR are regarded as having better antifouling performance [3,11].…”
Section: Resultsmentioning
confidence: 99%
“…Deionized water was permeated again as a feed and another pure water flux ( J 2 ) was determined. The flux recovery ratio ( FRR ), the total flux decline ratio ( DR t ), and irreversible flux decline ratio ( DR ir ) can be defined according to the references [1,3,44]:FRR=J2J0×100%, DRt=J0J1J0×100%, DRnormalinormalr=J0J2J0×100%.…”
Section: Methodsmentioning
confidence: 99%